Korea Pathfinder Lunar Orbiter (KPLO) Operation: From Design to Initial Results - Jeon, Moon-Jin; Cho, Young-Ho; Kim, Eunhyeuk; Kim, Dong-Gyu; Song, Young-Joo; Hong, SeungBum; Bae, Jonghee; Bang, Jun; Yim, Jo Ryeong; Kim, Dae-Kwan (Journal of astronomy and space sciences, 2024)
Korea Pathfinder Lunar Orbiter (KPLO) is South Korea’s first space exploration mission, developed by the Korea Aerospace Research Institute. It aims to develop technologies for lunar exploration, explore lunar science, and test new technologies. KPLO was launched on August 5, 2022, by a Falcon-9 launch vehicle from cape canaveral space force station (CCSFS) in the United States and placed on a ballistic lunar transfer (BLT) trajectory. A total of four trajectory correction maneuvers were performed during the approximately 4.5-month trans-lunar cruise phase to reach the Moon. Starting with the first lunar orbit insertion (LOI) maneuver on December 16, the spacecraft performed a total of three maneuvers before arriving at the lunar mission orbit, at an altitude of 100 kilometers, on December 27, 2022. After entering lunar orbit, the commissioning phase validated the operation of the mission mode, in which the payload is oriented toward the center of the Moon. After completing about one month of commissioning, normal mission operations began, and each payload successfully performed its planned mission. All of the spacecraft operations that KPLO performs from launch to normal operations were designed through the system operations design process. This includes operations that are automatically initiated post-separation from the launch vehicle, as well as those in lunar transfer orbit and lunar mission orbit. Key operational procedures such as the spacecraft’s initial checkout, trajectory correction maneuvers, LOI, and commissioning were developed during the early operation preparation phase. These procedures were executed effectively during both the early and normal operation phases. The successful execution of these operations confirms the robust verification of the system operation.